Seroepidemiology of Chikungunya Fever in Dhaka, Bangladesh: A Crosssectional Study - Shourav, Abiral Hasib; Mahbub, M Murshida; Yasmin, Mahmuda; Ahsan, Chowdhury Rafiqul; Nessa, Jamalun (Bangladesh Journal of Microbiology, 2022)
Chikungunya fever (CHIKF) is a mosquito-borne febrile illness caused by the Chikungunya virus (CHIKV). Bangladesh has documented several outbreaks of CHIKF since it was first reported in 2008. The latest CHIKF outbreak occurred in the Dhaka in 2017. In this study, a serosurvey of the 2017 outbreak was conducted during its peak. The study involved the assessment of CHIKV immunoreactions among participants suffering from CHIKF related symptoms. One hundred blood samples were collected from patients suffering from CHIKF-associated symptoms and were subsequently tested for the presence of anti-CHIKV IgM and/or IgG antibodies. Data based on clinical symptoms and the demographics of the participants were recorded and analyzed. Seventy-four percent of the studied patients (n = 100) possessed anti-CHIKV antibodies. Among this seropositive group (n = 74), almost 62% contained anti-CHIKV IgM and IgG antibodies, whereas 10% contained only anti-CHIKV IgM antibodies indicating recent infection. Anti-CHIKV IgG antibodies were found in 28% of patients. Among the symptoms examined, polyarthralgia showed a highly significant relationship (P < 0.001), whereas high fever and the presence of rash demonstrated a significant association with CHIKV seropositivity (P < 0.05). Discoveries made on this research can better help public health officials to gain a comprehensive insight into the seroepidemiology of the condition based in the city and maintain constant vigilance against any future outbreak. Bangladesh J Microbiol, Volume 38, Number 2, December 2021, pp 79-85